Podcasting as a tool in the development of public speaking skills - Ainol Haryati, Ibrahim (2012)
This study employed the quasi-experimental, pretest-posttest nonequivalent control group design to investigate the effects of podcasting in reducing anxiety and improving public speaking skills of ESL learners.Eighty-two students were involved in the study They were enrolled in the fifth semester of the Bachelor in Civil Engineering program at Universiti Malaysia Pahang This sample was divided into three groups Two groups were subjected to experimental treatment and one group was assigned as the control group. The Personal Report of Public Speaking Anxiety (PRPSA) was administered as the pre-test and post-test to measure the students' level of anxiety pertaining to public speaking. The Competent Speaker Speech Evaluation Form (CSSEF) was used as an instrument to measure the students' public speaking performance at pre-test and post-test.Students' attitude and perceptions on the use of podcasting in the public speaking class were explored using a questionnaire survey,and augmented with observations,group interviews and examination of the entries made in their respective websites.The overall PRPSA scores revealed that the students in all three groups demonstrated a significant reduction in their anxiety level,from pre-test to post-test.Pairwise comparisons between groups revealed that there was no significant difference between the groups.Similar results were obtained with the CSSEF,where the students in all three groups made significant improvements in their public speaking performance.Again,pairwise comparisons between groups revealed that there was no significant difference between the groups.However,at post-test,the experimental group demonstrated a negative correlation between speech performance and speech This study employed the quasi-experimental, pretest-posttest nonequivalent control group design to investigate the effects of podcasting in reducing anxiety and improving public speaking skills of ESL learners. Eighty-two students were involved in the study. They were enrolled in the fifth semester of the Bachelor in Civil Engineering program at Universiti Malaysia Pahang. This sample was divided into three groups. Two groups were subjected to experimental treatment,and one group was assigned as the control group.The Personal Report of Public Speaking Anxiety (PRPSA) was administered as the pre-test and post-test to measure the students'level of anxiety pertaining to public speaking.The Competent Speaker Speech Evaluation Form (CSSEF) was used as an instrument to measure the students' public speaking performance at pre-test and post-test.Students'attitude and perceptions on the use of podcasting in the public speaking class were explored using a questionnaire survey, and augmented with observations,group interviews and examination of the entries made in their respective websites.The overall PRPSA scores revealed that the students in all three groups demonstrated a significant reduction in their anxiety level,from pre-test to post-test.Pairwise comparisons between groups revealed that there was no significant difference between the groups.Similar results were obtained with the CSSEF,where the students in all three groups made significant improvements in their public speaking performance.Again, pairwise comparisons between groups revealed that there was no significant difference between the groups.However,at post-test, the experimental group demonstrated a negative correlation between speech performance and speech anxiety,where students' speech performance improved as their level of anxiety decreased. A similar relationship between the two variables was not evident in the control group.Further investigations revealed that although the students in the experimental groups agreed that podcasting should be incorporated in future public speaking classes,they faced technical-related difficulties such as inconsistent speed and intermittent access to the Internet during the study,thus the "anytime, anywhere" maxim for podcasting was not applicable in this situation. Anxiety,wherestudents'speechperformance improved as their level of anxiety decreased.A similar relationship between the two variables was not evident in the control group.Further investigations revealed that although the students in the experimental groups agreed that podcasting should be incorporated in future public speaking classes, they faced technical-related difficulties such as inconsistent speed and intermittent access to the Internet during the study, thus the "anytime, anywhere" maxim for podcasting was not applicable in this situation.